2017
DOI: 10.1590/0104-07072017001400016
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Errors: A Study of the Current Literature

Abstract: Objective:to characterize what the current literature states about nursing errors, with a specific review on how these errors are communicated to society by the media.Method: a qualitative documental research, characterized as an integrative literature review, performed using four databases and guided by a formal protocol, in the period from 2011 to 2015, by two independent collaborators. The analysis of the studies occurred through the analysis of thematic content articulated with the resources of the Atlas.t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
22
0
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 30 publications
(75 reference statements)
6
22
0
11
Order By: Relevance
“…It observed that the characteristics of the patients themselves can be included in the causes, which in HD are considered critical, as well as fatigue and stress, which may be related to the intensity of the activities and to the high turnover of the patients. 17 The type of AE with the highest prevalence found in this study is similar to the data found in literature, which also indicates medication error in patients on hemodialysis treatment as the most common type of AE . 4,14,[18][19] The National Agency of Sanitary Surveillance defines medication error as any preventable event that may lead to the inappropriate use of a medication under the control of the health team or even the patient himself, that leads to, or has the potential to lead to, harm to the patient.…”
Section: Discussionsupporting
confidence: 90%
“…It observed that the characteristics of the patients themselves can be included in the causes, which in HD are considered critical, as well as fatigue and stress, which may be related to the intensity of the activities and to the high turnover of the patients. 17 The type of AE with the highest prevalence found in this study is similar to the data found in literature, which also indicates medication error in patients on hemodialysis treatment as the most common type of AE . 4,14,[18][19] The National Agency of Sanitary Surveillance defines medication error as any preventable event that may lead to the inappropriate use of a medication under the control of the health team or even the patient himself, that leads to, or has the potential to lead to, harm to the patient.…”
Section: Discussionsupporting
confidence: 90%
“…This might lead to the conclusion that nursing is the professional category that is most directly involved in care errors that affect the “first victim”. These studies identify a need to promote improvements in work environments and adequate staffing to safely assist patients in meeting their needs (De Freitas et al, ; Forte, Pires, Padilha, & Martins, ).…”
mentioning
confidence: 99%
“…However, weaknesses and potential flaws in this process are noted due to the large number of drugs and nursing procedures to be performed with patients in a work shift, leading to constant disruptions at the time of drug preparation and administration. These findings are supported by a number of studies indicating that work overload, which results in the hasty performance of tasks, stress and diminished attention, and distractions are among the main risk factors for the administration of wrong drugs (12)(13)(14)(15) .…”
Section: Discussionmentioning
confidence: 56%